WASATHIYYAH DAN FIQIH KEBANGSAAN (Strategi Pendidikan Islam dalam Merawat Keberagaman) - Khusnul Khotimah; achmad Ismail (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2025)
This study examines the values of moderation in Islam from the perspectives of national fiqh and sociology, as well as their implementation in Islamic education in Indonesia. Moderation in Islam, rooted in the teachings of the Qur’an and Hadith, encompasses values such as Tawassuth (balance), Tasamuh (tolerance), I’tidal (justice), and Musawah (equality). Although these values form the fundamental basis of Islamic teachings, their implementation in the educational sphere still faces challenges, such as radicalization through social media and the uneven dissemination of moderation education across institutions. Nevertheless, Islamic education plays a crucial role in instilling the values of moderation that can shape students’ character to be tolerant and open to diversity. The implementation of moderation in the education sector requires collaboration between curriculum development, educators, and national policies. This study also provides recommendations to strengthen the values of moderation within the Islamic education system through moderate Islamic literacy, structured training, and a more systematic curriculum.